Perancangan program aplikasi perpustakaan berbasis java pada smp Al-Muhajirin - Dian Nazelliana; Purwanti Purwanti (Journal of Information System, Informatics and Computing, 2021)
The purpose of the research entitled "Designing Java-Based Library Application Programs at the AL-MUHAJIRIN Middle School Library" which was designed with Netbeans IDE, XAMPP, and MySQL as the database, namely to assist the processes of transaction activities in the library and facilitate librarians in making student data reports, book data, loan data, return data, so there is no need to use paper media anymore. The design of this library application program goes through several stages, namely the requirements stage, the analysis stage, the design stage and implementation stage, and the deployment stage. In the process of making research reports and collecting data, the authors use qualitative research methods in the form of literature studies, observations and interviews conducted at Al-Muhajirin Junior High School located in Depok. To analyze this application, the author uses object-oriented analysis with Unified Modeling Language (UML).